Dimensionando o mercado para hipoteca reversa no Brasil - Igor Ferreira; Rodrigo Mendes Pereira; Mario Jorge Mendonça; Beatriz Pinna (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– Reverse mortgage is a financial instrument that allows elderly homeowners to enjoy an additional income until the end of their lives, when the property is taken by the financial institution that provided the benefit. Based on data from the continuous PNAD of 2019 and considering the property owners who live alone at home or who live with their spouse as the potential market, this study aims to determine the size of the market for reverse mortgage in Brazil. One important goal is to identify the monthly volume of credit that would enter the economy. Our methodology has the following steps. We estimate a regression with PNAD's non-restricted sample to determine the rent price, obtaining the value of the properties for the restricted sample of eligible households, through a rule on the predicted value of the rent. With the predicted value of the property, we apply a model that estimates the monthly reverse mortgage benefit compatible with the financial and actuarial equilibrium of the system. The results show that the average reverse mortgage benefit is R 1,100 while the monthly credit volume that can be generated is close to R 9 billion. Considering the existing pressure on the social security system, in which the Continuous Benefit Program (BPC) is inserted, we evaluated the potential for reducing public spending with BPC in case part of the beneficiaries of this program chose to join the reverse mortgage.
Keywords: R21; R31; G21; 330; reverse mortgage; weight least square; perpetuity; life expectance; actuarial equilibrium